2019
DOI: 10.4062/biomolther.2018.231
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Herbs Effective Against Atherosclerosis: Classification According to Mechanism of Action

Abstract: Atherosclerosis is a widespread and chronic progressive arterial disease that has been regarded as one of the major causes of death worldwide. It is caused by the deposition of cholesterol, fats, and other substances in the tunica intima which leads to narrowing of the blood vessels, loss of elasticity, and arterial wall thickening, thus causing difficulty in blood flow. Natural products have been used as one of the most important strategies for the treatment and prevention of cardiovascular diseases for a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 72 publications
(96 reference statements)
1
20
0
Order By: Relevance
“…us, drugs including medicinal plants with hypolipidemic/antihyperlipidemic activities could equally be considered antiatherosclerotic and cardioprotective [108][109][110]. us, the hypolipidemic/antihyperlipidemic activity of CVE observed in this study is in tandem with those previously reported for Clerodendrum volubile and related species [32,80,[111][112][113][114].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…us, drugs including medicinal plants with hypolipidemic/antihyperlipidemic activities could equally be considered antiatherosclerotic and cardioprotective [108][109][110]. us, the hypolipidemic/antihyperlipidemic activity of CVE observed in this study is in tandem with those previously reported for Clerodendrum volubile and related species [32,80,[111][112][113][114].…”
Section: Discussionsupporting
confidence: 85%
“…It is equally well documented in the literature that a direct relationship exists between hypercholesterolemia and hyperlipidemia and atherosclerosis which is considered as a major cause of cardiovascular disease, especially coronary heart disease [ 105 107 ]. Thus, drugs including medicinal plants with hypolipidemic/antihyperlipidemic activities could equally be considered antiatherosclerotic and cardioprotective [ 108 110 ]. Thus, the hypolipidemic/antihyperlipidemic activity of CVE observed in this study is in tandem with those previously reported for Clerodendrum volubile and related species [ 32 , 80 , 111 – 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of 33 compounds out of 35 did not surpass 140Ų. Both Formic acid, (3,5-dinitrophenyl)amino-, [3-(ethoxycarbonyl)prop-2-yl] ester (PubChem ID: 552329) and 4,9a-Bis(acetyloxy)-3-[(acetyloxy)methyl]-4a,7b-dihydroxy 1,6,1b,4,4a,5,7a,7b,8,9,4]benzo [1,2-E]azulen-9-yl acetate # (PubChem ID: 538181) were not accepted within the border. This information was exhibited in Table 2.…”
Section: Potential Bioactive Compounds From Sbmentioning
confidence: 99%
“…The natural product extracts are relatively safe, although some include unexpected adverse side effects such as headache, vomiting, dizziness, and constipation [8]. Also, medicinal herbal plants have been considered one of the most substantial therapeutics for alleviating and preventing congestive heart failure, including AS [9]. The medicinal mushrooms categorized into natural products also have diverse pharmacological effects, including antimicrobial, antitumor, anti-in ammatory, and antiatherogenic activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The natural product extracts are relatively safe, including unexpected adverse side effects such as headaches, vomiting, dizziness, and constipation (Ekor, 2014). Also, medicinal herbal plants have been considered one of the most substantial therapeutics for alleviating and preventing congestive heart failure, including AS (Kim & Shim, 2019). The medicinal mushrooms categorized into natural products also have diverse pharmacological effects, including antimicrobial, antitumor, anti‐inflammatory, and anti‐atherogenic activities (Lindequist et al., 2005).…”
Section: Introductionmentioning
confidence: 99%